PENGARUH PUTARAN TERHADAP KEPERLUAN BAHAN BAKAR DAN THRUST TURBO JET SPEY MK 555.15H - Juli Mrihardjono; Sutomo - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
Turbo Jet SPEY 555-15 is Rolls Royce's production, which is used by Concord Air Plane. This  engine  has external  flowing  by-poss channel  with twin spool axial compressor ond be moved by coaxial turbine shaft. This engine has four low pressure stages and twelve high pressure stages compressor to supply the high energy of air in order to have high internal  combustion energy in combustion chaiber, This research would like to know the influence of rotation (rpm) to fuel consumption and trust of theengine. The result  of this research have indicated that increasing of rotations will cause increasing fuel consumption and trust  but for fuel  consumption (FC) will decrease up to 5089 rpm. Fuel consumption (FC)  will be constant if the speed more than 5089  rpm more than 8501 rpm,  the fuel consumption and trust utill be effective.